Pemanfaatan Ecobrick Sebagai Media Stimulasi Numersi Anak Usia Dini - Marom, Nailil; Aryani, Nini; Herwina, Herwina (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This research is motivated by the importance of developing early childhood numeracy skills through concrete and sustainable media. The purpose of this study is to describe the implementation of ecobrick activities in stimulating children's numeracy skills, analyze their impact, and identify challenges and opportunities in their implementation. This study uses a descriptive qualitative approach. Data was collected through observations, interviews, and documentation of children's activities when processing plastic waste into ecobricks. The results of the study show that ecobrick activities significantly stimulate children's numeracy skills through three main aspects: 1) The use of numbers and symbols, where children learn to recognize and count the number of bottles and garbage concretely; 2) Contextual problem solving, through estimation of material needs and comparison of sizes (weight and length); and 3) Simple data-driven decision-making in project work. The main challenge found is the consistency of material availability, while the opportunity lies in the integration of environmental education in the PAUD curriculum. In conclusion, ecobricks are effective as an interactive numeracy learning medium while instilling the character of caring for the environment from an early age.